1997
DOI: 10.1002/cjce.5450750108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of peracetic acid decomposition: Part I: Spontaneous decomposition at typical pulp bleaching conditions

Abstract: Peracetic acid may become one of alternative non-chlorine bleaching chemicals in the production of fully bleached chemical pulps. In this paper, the stability of peracetic acid was studied in an aqueous solution under conditions most likely encountered in the industrial processes. It was found that three potential reactions, namely i) the spontaneous decomposition, ii) the hydrolysis and iii) the transition metal catalyzed decomposition, are responsible for the consumption of peracetic acid. Furthermore, the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 3 publications
(2 reference statements)
5
56
2
Order By: Relevance
“…Baldry (1983) exposed S. cerevisiae to different concentrations of PAA, however different temperatures and pH were used (5.0, 6.5 and 8.0), versus our experiment, where pH was not a factor to control since only deionized water was used to prepare the PAA solutions that were added to the flasks (in vitro experiments) and where temperature was stable during the whole time of our experiment. Baldry (1983) found that the efficacy of PAA against two strains of S. cerevisiae decreases with increasing pH, since when alkalinity of the solution increases, peracetic acid is hydrolyzed to form acetic acid and hydrogen peroxide (Yuan et al, 1997). Accordingly, Baldry (1983) found that resistance among genera (particularly between Z. bailii and S. cerevisiae) is variable, this latter aspect also found in our experiments.…”
Section: In Vitro Reduction Of Yeastsupporting
confidence: 81%
See 1 more Smart Citation
“…Baldry (1983) exposed S. cerevisiae to different concentrations of PAA, however different temperatures and pH were used (5.0, 6.5 and 8.0), versus our experiment, where pH was not a factor to control since only deionized water was used to prepare the PAA solutions that were added to the flasks (in vitro experiments) and where temperature was stable during the whole time of our experiment. Baldry (1983) found that the efficacy of PAA against two strains of S. cerevisiae decreases with increasing pH, since when alkalinity of the solution increases, peracetic acid is hydrolyzed to form acetic acid and hydrogen peroxide (Yuan et al, 1997). Accordingly, Baldry (1983) found that resistance among genera (particularly between Z. bailii and S. cerevisiae) is variable, this latter aspect also found in our experiments.…”
Section: In Vitro Reduction Of Yeastsupporting
confidence: 81%
“…PAA solutions are produced from the reaction of acetic acid or acetic anhydride with hydrogen peroxide in the presence of sulfuric acid, which functions as a catalyzing agent (Vandekinderen et al, 2009). In spontaneous decomposition, peracetic acid is decomposed to form acetic acid and oxygen, thus representing a loss of oxidation power (Yuan et al 1997). It acts primarily on lipoproteins in the cell membrane, and it may be equally effective against outer membrane lipoproteins (Silveira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the peracid formulation, namely the peracid/H 2 O 2 ratio and possible stabilizers have an effect on the decomposition rate [104]. In a concentrated solution, the decomposition of peracid occurs by three mechanisms: hydrolysis, spontaneous decomposition, and transition-metal catalyzed decomposition (Reactions 9, 10, and 11, respectively) [106][107][108]. The kinetics and exact reaction mechanisms of the spontaneous decomposition and hydrolysis were presented by Zhao et al [36,109].…”
Section: Reactions In Aqueous Media: Disinfection and Oxidation Mechamentioning
confidence: 99%
“…This finding could be explained as follows; crystallographic orientation is well known to significantly affect the electrocatalytic properties of electrodes toward several electrochemical reactions [26][27][28][29]. For instance, the oxygen reduction reaction (ORR), and consequently H 2 O 2 reduction, is inherently dependent on the crystallographic orientation of the Au electrode [30]. The present study is the first report regarding the dependence of PAA reduction on the crystallographic orientation of gold electrode.…”
Section: Electrochemical Behavior Of Paa and H 2 O 2 Mixturementioning
confidence: 84%